Academics as orchestrators of continuous innovation ecosystems: towards a fourth generation of CI initiatives. (1st January 2015) - Gastaldi, Luca; Appio, Francesco Paolo; Martini, Antonella; Corso, Mariano
In this paper, we shed light on why academics are in one of the best positions to orchestrate inter–organisational initiatives of continuous innovation (CI) within an innovation context that is shifting towards an open collaborative ecosystem mode. Two rationales seem to explain the potential key role of academics within a CI ecosystem: 1) their independence; 2) their compliance to CI ecosystem's purposes - independently by its type. The implications of the five papers invited to be part of the special issue, and formerly presented at the 14th International CINet Conference in Nijmegen, The Netherlands, are also discussed.